2018
DOI: 10.3168/jds.2017-14111
|View full text |Cite
|
Sign up to set email alerts
|

Milk yield, quality, and coagulation properties of 6 breeds of goats: Environmental and individual variability

Abstract: Goat milk and cheese production is continuously increasing and milk composition and coagulation properties (MCP) are useful tools to predict cheesemaking aptitude. The present study was planned to investigate the extension of lactodynamographic analysis up to 60 min in goat milk, to measure the farm and individual factors, and to investigate differences among 6 goat breeds. Daily milk yield (dMY) was recorded and milk samples collected from 1,272 goats reared in 35 farms. Goats were of 6 different breeds: Saan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
74
3

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(103 citation statements)
references
References 41 publications
26
74
3
Order By: Relevance
“…Our sample presents a between-farm variability that ranges from 17.8% to 20.6% for fat and milk yield, respectively. A similar effect power of farms on the yield and quality of the milk of 6 breeds of goats has been reported to range from around 20% to 45% (Vacca et al 2018). As reported by Nolan and Heinzen (2017), as the sample size increases, a normal distribution of scores will more closely resemble a normal curve, hence reducing the effects of violating the normality assumption.…”
Section: Discussionsupporting
confidence: 72%
“…Our sample presents a between-farm variability that ranges from 17.8% to 20.6% for fat and milk yield, respectively. A similar effect power of farms on the yield and quality of the milk of 6 breeds of goats has been reported to range from around 20% to 45% (Vacca et al 2018). As reported by Nolan and Heinzen (2017), as the sample size increases, a normal distribution of scores will more closely resemble a normal curve, hence reducing the effects of violating the normality assumption.…”
Section: Discussionsupporting
confidence: 72%
“…The effects of animal factors (DIM, parity, and breed) and farm were included in the statistical model to correct the estimation for the effect of milk composition on coagulation, curd firming, and syneresis processes. In the present study, these are reported only in the results because they have been discussed in depth in previous studies on the same data set (Vacca et al, 2018a;Pazzola et al, 2018). Briefly, DIM affected almost all coagulation traits.…”
Section: Effect Of Individual Animal Factors Farm and Breed On Rennmentioning
confidence: 85%
“…A total of 1,272 goats belonging to 6 breeds, reared in 35 farms distributed over the island of Sardinia (Italy) were sampled once for milk composition. Details of farm characteristics and description of the breeds are reported by Vacca et al (2018a).…”
Section: Milk Sampling and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The milk pH is a popular indirect indicator of mastitis [21,22]. The physiochemical quality of milk from different goat breeds was analyzed by Vacca et al [32]. They found that the mean pH measured 6.72, but it varied from 6.67 to 6.76 between breeds.…”
Section: Discussionmentioning
confidence: 99%